KEPATUHAN WAJIB PAJAK: PENGARUH SISTEM E-FILING, SANKSI PAJAK, DAN SOSIALISASI PAJAK DIMODERASI OLEH KUALITAS PELAYANAN FISKUS - Nur Rahmah Sari (Universitas Islam Negeri Alauddin Makassar, 2021)
This study was conducted to examine the effect of implementing e-filing system, tax sanctions, and tax socialization on taxpayer compliance moderated by the quality of fiscus services. This study is a quantitative study with with an associative approach. Data was collected by distributing questionnaires to the total of 100 taxpayers at KPP Pratama North Makassar. Data were analyzed using multiple linear regression analysis. The result showed the e-filing system, tax sanctions, and tax socialization had a significant positive effect on taxpayer compliance. This study also found tha the quality of fiscus services was able to moderate the effect of tax sanction on taxpayer compliance, but din not moderate the effect of the e-filing system and tax socialization on taxpayer compliance. Keyword: E-Filing System, Tax Sanctions, Tax Socialization, Tax Compliance, Fiscus Services Quality.